Phenotypic and Genomic Properties of Chitinispirillum alkaliphilum gen. nov., sp. nov., A Haloalkaliphilic Anaerobic Chitinolytic Bacterium Representing a Novel Class in the Phylum Fibrobacteres - Sorokin, Dimitry Y.; Rakitin, Andrey L.; Gumerov, Vadim M.; Beletsky, Alexey V.; Sinninghe Damsté, Jaap S.; Mardanov, Andrey V.; Ravin, Nikolai V. (Frontiers in Microbiology, 2016)
Anaerobic enrichment from sediments of hypersaline alkaline lakes in Wadi el Natrun (Egypt) with chitin resulted in the isolation of a fermentative haloalkaliphilic bacterium, strain ACht6-1, growing exclusively with insoluble chitin as the substrate in a sodium carbonate-based medium at pH 8.5-10.5 and total Na+ concentrations from 0.4 to 1.75 M. The isolate had a Gram-negative cell wall and formed lipid cysts in old cultures. The chitinolytic activity was associated with cells. Analysis of the 4.4 Mb draft genome identified pathways for chitin utilization, particularly, secreted chitinases linked to the cell surface, as well as genes for the hydrolysis of other polysaccharides and fermentation of sugars, while the genes needed for aerobic and anaerobic respiration were absent. Adaptation to a haloalkaliphilic lifestyle was reflected by the gene repertoire encoding sodium rather than proton-dependent membrane-bound ion pumps, including the Rnf-type complex, oxaloacetate decarboxylase, V-type ATPase and pyrophosphatase. The phylogenetic analysis using 16S rRNA gene and ribosomal proteins indicated that ACht6-1 forms a novel deep lineage at the class level within the bacterial candidate division TG3. Based on phylogenetic, phenotypic and genomic analyses, the novel chitinolytic bacterium is described as Chitinispirillum alkaliphilum gen. nov., sp. nov., within a novel class Chitinispirillia that could be included into the phylum Fibrobacteres.